Persepsi Mahasiswa Keperawatan Tentang Sistem Pembelajaran Blok dan Non-blok - Permatasari, Bima; Elita, Veny; Dewi, Wan Nishfa (Cerdika: Jurnal Ilmiah Indonesia, 2022)
The determining student's perceptions toward learning dimensions including the learning duration, schedule, mastery of the material, and the grouping of lesson hours which are applied for both systems. Method: The study uses a descriptive design and it is conducted at the faculty of nursing, University of Riau. The questionnaire is used as an instrument which is designed by Pratiwi and has been tested for validity and reliability. The result showed that the majority of respondents were 21 years old as many as 108 respondents (35,2%) and female respondents 281 respondents (91,5%). Based on the result of the study, it was found in the positive perception block learning system, there were lectures scheduled for as 190 respondents (61,9%) And mastery of the material by 240 respondents (78.2%). Whereas in the non-block learning systems, there were positive perceptions of students in the learning time as 177 respondents (57,7%) and grouping of lesson hours as 211 respondents (68,7%). Block and non-block learning systems on each indicator still have advantages and disadvantages so learning has not been running optimally. An educational institution is hoped to be able to evaluate the duration of learning on the block learning system and learning schedule on non-block learning systems to run it effectively and optimally.